2021
DOI: 10.3389/fcell.2021.694675
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis Induces Proinflammatory Cytokine Production in Mouse Macrophages via TLR9-Mediated p38 and ERK Signaling Pathways

Abstract: Giardia duodenalis, also known as Giardia lamblia or Giardia intestinalis, is an important opportunistic, pathogenic, zoonotic, protozoan parasite that infects the small intestines of humans and animals, causing giardiasis. Several studies have demonstrated that innate immunity-associated Toll-like receptors (TLRs) are critical for the elimination of G. duodenalis; however, whether TLR9 has a role in innate immune responses against Giardia infection remains unknown. In the present study, various methods, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 71 publications
(87 reference statements)
0
13
0
Order By: Relevance
“…38 The production of TNF-a, IL-6 and IL-12p40 induced by G. lamblia was significantly influenced by ERK and p38 signals via TLR2 or TLR9. 12,15 Our data indicated that the NOD2-Rip2 signaling pathway regulated the production of these cytokines via the NF-jB and ERK signaling pathways, suggesting ERK signaling may play a key role in regulating cytokine secretion in PMs challenged with G. lamblia.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…38 The production of TNF-a, IL-6 and IL-12p40 induced by G. lamblia was significantly influenced by ERK and p38 signals via TLR2 or TLR9. 12,15 Our data indicated that the NOD2-Rip2 signaling pathway regulated the production of these cytokines via the NF-jB and ERK signaling pathways, suggesting ERK signaling may play a key role in regulating cytokine secretion in PMs challenged with G. lamblia.…”
Section: Discussionmentioning
confidence: 75%
“…20 NOD2-Rip2 signaling pathway regulated the NF-jB, p38, c-Jun N-terminal kinase and ERK signals during porcine reproductive and respiratory syndrome virus infection, 39 suggesting that signaling pathways controlled by NOD2 vary in different pathogen infections. In addition, both TLR9 15 and NOD2 regulated the activation of ERK signaling in macrophages challenged with G. lamblia. However, TLR9 regulated the activation of the p38 signaling pathway, but not the NF-jB p65 pathway, 15 while NOD2 induced the activation of the NF-jB p65 pathway, but not the p38 signaling pathway.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations